2015
DOI: 10.1103/physrevb.91.075314
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed low-field electrically detected magnetic resonance

Abstract: We present pulsed electrically detected magnetic resonance (EDMR) measurements at low magnetic fields using phosphorus-doped silicon with natural isotope composition as a model system. Our measurements show that pulsed EDMR experiments, well established at X-band frequencies (10 GHz), such as coherent spin rotations, Hahn echoes, and measurements of parallel and antiparallel spin pair life times are also feasible at frequencies in the MHz regime. We find that the Rabi frequency of the coupled 31 P electron-nuc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…On the other hand, the ability to lithographically pattern structures on silicon surfaces could enable the design of sensor arrays which are highly scalable. As Dreher et al have shown previously, EDMR can be used to detect protons adsorbed onto the silicon surface, analogous to NMR measured by way of NV centers [21]. This coupling between interfacial P b0 defects and surface nuclear spin species has also been observed in dynamic nuclear polarization experiments [45,46].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…On the other hand, the ability to lithographically pattern structures on silicon surfaces could enable the design of sensor arrays which are highly scalable. As Dreher et al have shown previously, EDMR can be used to detect protons adsorbed onto the silicon surface, analogous to NMR measured by way of NV centers [21]. This coupling between interfacial P b0 defects and surface nuclear spin species has also been observed in dynamic nuclear polarization experiments [45,46].…”
Section: Discussionmentioning
confidence: 85%
“…Table II shows the parameters in these simulations. Dreher et al have reported singlet and triplet recombination time constants to be 15 ”s and 2 ms respectively in Si:P [21]. However the other rates for this system have not been measured to date.…”
Section: Wavelength-dependent Rate Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase cycling has been extensively studied in the context of Nuclear Magnetic Resonance [52,53] and ESR [54,55] experiments. Recently it was demonstrated for pEDMR [56] and since then it has been used in electrically-detected double electron-electron resonance, electron spin echo envelope modulation and inversion recovery [57,58,38,59,60], although its' general applicability has not been discussed.…”
Section: Hahn Echomentioning
confidence: 99%
“…As such, we can usually discuss the spin-dependent rates in terms of the product basis, consisting of parallel (j ""i; j ##i) and anti-parallel (j "#i; j #"i) pairs [32]. The introduction of exchange or dipolar coupling, real-time [37] readout, or low-field measurement [38] (when B 0 is comparable to the Overhauser field or zero-field splitting) will weaken the spin mixing between the singlet and T 0 states and modify the transient dynamics. These effects are beyond the scope of this paper.…”
Section: Weakly-coupled Pairsmentioning
confidence: 99%